DETERMINATION OF THE EFFECTIVE DOSE OF PHOSPHORUS IN LEMON EUCALYPTUS PLANTS (Corymbia citriodora) - Luis Soto-Gonzales, Jose; Valiengo-Valeri, Sergio [UNESP]; Cristina Pessoa-da-Cruz, Mara [UNESP]; Cesar de Paula, Rinaldo [UNESP]; Vulfrano Gonzalez-Fernandez, Jose (Colegio Postgraduados, 2022)
Phosphorus (P) is one of the most limiting nutrients for plant species and its intensive use can exhaust world reserves. In general, forest production is unviable without the availability of P. The objective of the study was to determine the effect of phosphate fertilization on plant growth of four families of lemon eucalyptus (Corymbia citriodora). Plants produced from seeds of four seed trees were used, which were subjected to seven doses of phosphorus: 0, 25, 50, 75, 100, 125 and 150 mg P dm(-3). The experiment was carried out in a 7 x 4 factorial arrangement, with four replicates and using containers with 5 dm(3) of a Red Eutropheric Latosol type soil. The response variables measured were monthly plant height, plant collar diameter at 90 d, dry biomass weight of leaves, roots, stems and branches, and phosphorus use efficiency of leaves. The variations of the characteristics evaluated as a function of phosphorus concentration were analysed by means of polynomial regression equations. Phosphate fertilization is necessary for the growth and development of C. citriodora plants. Plants of the four C. citriodora seed trees from different provenances responded differentially to phosphorus doses. It was found that the optimum amount of phosphorus ranges between 30 and 100 mg dm(-3) according to the characteristics evaluated and the seed tree.
Keywords: seed trees; forest fertilization; provenances; phosphorus doses; Corymbia citriodora